1999
DOI: 10.1034/j.1600-0420.1999.770621.x
|View full text |Cite
|
Sign up to set email alerts
|

Solitary fibrous tumor of the orbit, a poorly‐recognized orbital lesion

Abstract: ABSTRACT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…15,16 The review of the literature reveals a recent trend of rather rapid accumulation of the number of orbital SFTs, and so far more than 50 cases of orbital SFT have been reported in the English-language literature. [10][11][12][13][14][15][16][17][18][19][20][21] Bernardini et al 15 questioned the rarity of orbital SFT. According to these authors, thanks to the widespread use of immunohistochemical studies, the number of orbital SFTs has rapidly been increasing after 1994 when the first orbital SFT was reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15,16 The review of the literature reveals a recent trend of rather rapid accumulation of the number of orbital SFTs, and so far more than 50 cases of orbital SFT have been reported in the English-language literature. [10][11][12][13][14][15][16][17][18][19][20][21] Bernardini et al 15 questioned the rarity of orbital SFT. According to these authors, thanks to the widespread use of immunohistochemical studies, the number of orbital SFTs has rapidly been increasing after 1994 when the first orbital SFT was reported.…”
Section: Discussionmentioning
confidence: 99%
“…5,7,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Usually, the tumor is seen as a well-defined soft tissue mass with heterogeneously or homogeneously strong enhancement on CT and MR images. Occasional internal calcifications and necrosis have also been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, there are up to 50 SFTs of the orbit described [1,4,5,6,8,13,15,16,17,18,19,20,21,26,27,28,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46]. The aim of the present study is to present two cases and to review the current literature.…”
Section: Introductionmentioning
confidence: 95%
“…1 Eighteen solitary fibrous tumours have been reported to occur within the orbit, of which only one was located in the lacrimal gland fossa. 2,3 Only a single study reported two patients with involvement of the lacrimal sac. 4 Our case involves this rare tumour within the submucosa of the lacrimal sac with unique clinical and staining features.…”
Section: Sirmentioning
confidence: 99%